108k views
8 votes
What is the solution to the given system of equations. y = 4x - 3
y = -X- 13

User Rob Louie
by
5.4k points

1 Answer

2 votes
y = 4x - 3
y = -x - 13
Since both equations equal y, we will just substitute both equations to equal each other.
4x - 3 = -x - 13
+x on both sides
5x - 3 = -13
+3 on both sides
5x = -10
/5 on both sides
x = -2

Substitute x = -2 into one of the equations.
y = -x - 13
y = -(-2) - 13
y = 2 - 13
y = -11

To check answer, plug in both x and y values into one of the equations.
y = -x -13
-11 = -(-2) - 13
-11 = 2 - 13
-11 = -11

Answer:
x = -2
y = -11
User TheDbGuy
by
5.0k points